Uncommon sense : the heretical nature of science - Cromer, Alan, 1935-2005 (Oxford University Press, 1995)
Most people believe that science arose as a natural end-product of our innate intelligence and curiosity, as an inevitable stage in human intellectual development. But physicist and educator Alan Cromer disputes this belief. Cromer argues that science is not the natural unfolding of human potential, but the invention of a particular culture, Greece, in a particular historical period. Indeed, far from being natural, scientific thinking goes so far against the grain of conventional human thought that if it hadn't been discovered in Greece, it might not have been discovered at all. In Uncommon Se.